Assessing the Impact of Different Weed Management Techniques on Weed Density and Yield of Sesame (Sesamum indicum l.) Cultivation - Shrestha, Suwany Kiran; Karkee, Suraj Singh (Journal of the Plant Protection Society, 2024)
Sesame is a seed crop grown primarily for its oil. However, weeds severely affect the crop, resulting in poor performance in the field, making it crucial to control weeds at appropriate times. Field based research was conducted following a Randomized Complete Block Design (RCBD) with four replications to assess the effectiveness of various weed management strategies. The treatments were one hand weeding at 22 DAS, pendimethalin as a pre-emergence herbicide, two-hand weeding at 15 DAS followed by 30 DAS, and two checks (weed free and weedy checks). Crop parameters like height of the plant, leaves number, branches, capsule number, seed yield and yield determining characters were recorded. Similarly, weed population data and weed dry weight were recorded. Two-hand weeding at 15 DAS followed by 30 DAS reduced the total weed density and dry weight more effectively than the other treatments. Capsule number and seed yield (0.56 t/ha) were higher significantly in the same treatment, followed by one-hand weeding at 22 DAS (0.38 t/ha), with the least recorded under pre-emergence herbicides (0.20 t/ha). Therefore, the study suggests implementing a weed management practice involving two hand-weeding in 15 DAS followed by 30 DAS to ensure higher seed yield, lower weed density and lower weed dry matter.